Comparison between supra-cath and pigtail in drainage of liver abscess - Gupta, Poonam; Goel, Anubhav; Kumar, Rajesh (International Surgery Journal, 2017)
Background: A majority of patients with liver abscess respond rapidly to treatment with drugs but the remaining specially with complications will eventually require either percutaneous aspiration or percutaneous drainage for their resolution. For this, Ryle’s tubes and Pigtail catheters have been used for percutaneous drainage of abscess. Supra-Cath is the latest variety of catheter which can be used for this purpose. Our study compares supracath and pigtail application for management. Methods: We conducted a prospective randomized comparative study in the departments of Surgery and Radiology, UPUMS Saifai, Etawah, Uttar Pradesh. A rural tertiary care centre in total of 60 patients from August 2016 to April 2017. Results: Average age in PCD and SCD were 38 and 42 respectably. Male:female ratio was 23:7 in PCD group and 21:9 in SCD group. Average size of abscess was 6.7 cm in PCD group and 6.9 in SCD group. Amoebic liver abscess was 18 in PCD and 22 in SCD group. Pyogenic abscess was 12 in PCD and 8 in SCD group. Average time for removal of PCD was 9.7 days and 8.6 in SCD group. In follow, up six patient had residual abscess in PCD group and two in SCD group at one month interval and all resolved with conservative treatment. Conclusions: Supra-Cath is very useful catheter for effective and safe drainage of large liver abscess and can be used as an alternative to pigtail catheter if not available.